Potential and obstacles in the implementation of digitalization in tourism villages (case studies in Banceuy Traditional Villages) - Rini Andari; Yeni Yuniawati (Jurnal Pariwisata Pesona, 2023)
Digitalization has an important role in the current era as an implication of technological developments, it can be used as a tool to predict the future. Tourism villages can utilize digitalization to the process of marketing to make it easier for tourists when accessing information about tourist villages. This study was conducted to explore the potential that can be developed and maximized in supporting digitalization in tourism villages, as well as to find out what obstacles arise in the application of digitalization. The data collection technique used in this study is a data collection technique through observation and interviews which is then analyzed using thematic data analysis. The results of the study found several potential applications of digitalization that can be developed such as the use of social media, websites, as well as the existence of several young people who already know applications to create content such as Lightroom Mobile, Capcut, and Pixellab. Unfortunately, there are two things that hinder the implementation of digitalization in the Banceuy Traditional Village, namely the limited internet network and the lack of quality of human resources owned. The development of the findings of this study is expected to be able to become material for evaluation and study for academics and practitioners in general, and specifically for local governments, managers, and the people of Banceuy Traditional Village in terms of implementing digitalization in tourism villages. So that in the future it will support the development of Banceuy Traditional Village as a superior tourist village destination